Silicon Affects Plant Stoichiometry and Accumulation of C, N, and P in Grasslands - Hao, Qian; Yang, Shilei; Song, Zhaoliang; Li, Zichuan; Ding, Fan; Yu, Changxun; Hu, Guozheng; Liu, Hongyan (Frontiers in Plant Science, 2020)
Silicon (Si)plays an important role in improving soil nutrient availability and plant carbon (C) accumulation and may therefore impact the biogeochemical cycles of C, nitrogen (N) and phosphorus (P) in terrestrial ecosystems profoundly.However, research on this process in grassland ecosystems is scarce, despite the fact that these ecosystems are one of the most significant accumulators of biogenic Si (BSi). In this study, we collected the aboveground parts of four widespread grasses and soil profile samples in northern China andassessed the correlationsbetween Si concentrations andstoichiometry and accumulation of C, N and P in grassesatthe landscape scale. Our results showed that Siconcentrationsin plants were significantly negatively correlated (p<0.01) with associated C concentrations. There wasno significant correlation between Si and N concentrations. It is worth noting thatsince the Si concentration increased, the P concentration increased from less than 0.10% to more than 0.20% (dw) and therefore C:P and N:P ratios decreased concomitantly. Besides, the soil noncrystalline Si played more important role in C, N and P accumulation than other environmental factors (e.g., MAT, MAP and altitude). These findings indicate that Si may facilitate grasses in adjusting the utilisation of nutrients (C, N and P) and may particularlyalleviate P deficiency in grasslands. We conclude that Si positively alters the concentrationsand accumulation of C, N and Plikelyresulting in the variationof ecological stoichiometry in both vegetation and litterdecomposition in soils. This study further suggests that the physiologicalfunction of Si is an important but overlooked factor in influencing biogeochemical cycles of C and P in grassland ecosystems.